Isolation and screening for limonin‐producing endophytic bacteria from Citrus maxima (Burm.) Merr. cv. Shatian Yu. (9th January 2019) - Zhang, Jinhua; Zang, Sanli; Bai, Baoqing; Fan, Sanhong
Abstract: Limonin, a compound of highly oxidized triterpenoids, has potential functions in preventing or slowing the occurrences of many diseases. In this study, five different bacterial strains were isolated and identified from Citrus maxima (Burm.) Merr. cv. Shatian Yu. Morphological characteristics and 16S rRNA gene sequencing identified them as Bacillus spp, in which two limonin‐producing endophytes named P and P9 were discovered by high‐performance liquid chromatography and mass spectrometry using an inorganic salt medium and two natural media; also the production was greater in natural medium 1 (4.377 and 0.299 mg/L, respectively) than in natural medium 2 (0.159 and 0.025 mg/L, respectively). The growth and fermentation characteristics of strain P were studied, and during the liquid cultivation of Bacillus sp. P, limonin began to accumulate at the eighth hour in the inorganic salt medium, peaked at the 16th hour, and then decreased sharply. Single‐factor experiments revealed that the optimum fermentation conditions for limonin production included 14‐H‐old cells, 15% inoculum, and 3 g/L glucose.